Rancang Bangun Sistem Pintu Antisipasi Covid-19 Dengan Sanitizer Otomatis Menggunakan Sensor Ultrasonik Arduino - aji nikmal maulaawa (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Covid-19 is a new type of disease caused by a virus from the SARS-CoV-2 group and can also be called a corona virus. Coronavirus (Covid-19). The plan to prevent the spread of this virus is to use health protocols (wearing masks, maintaining distance, and always washing hands). This design aims to design and construct Doors with automatic sanitizers to reduce the spread of the Covid-19 virus. This tool runs on the Arduino ultrasonic sensor to detect the hand at a certain distance, then the servo will pull the lever and release the sanitizer liquid, then the door will automatically open. Sanitizers currently circulating today are still manual, and if they are still used and widely used for people it is possible to transmit and spread the dangerous Covid-19 virus. These factors make it necessary to make an effort on automatic sanitizers like this to minimize the potential for the spread of Covid-10, which can maintain health and cleanliness. The creation of this tool is an effort to change the work design of the system on the sanitizer, starting from manual to automatic, and cleaning is safer.